2013
DOI: 10.1017/s147895151300014x
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional patients: Narratives of connections

Abstract: The importance of connections in these illness narratives was richly illustrated. These issues often are overlooked in clinical settings; yet they are of crucial importance to the health and well-being of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The challenge of the choice for a theoretical framework that can help studying and interpreting HP cases from a multidisciplinary perspective, lies in the absence of developed theoretical approaches that match the existing data (Levin, 2020 ). Reports on remarkable recoveries range between cases that are (un-)related to HP but are medically verified (Engebretson et al, 2014 ), cases that are described on the Lourdes pilgrimage site (François et al, 2014 ) and self-reported narrative accounts of patients, to name just a few. The authors who endeavour to provide an explanation for HP, usually take an eclectic approach.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The challenge of the choice for a theoretical framework that can help studying and interpreting HP cases from a multidisciplinary perspective, lies in the absence of developed theoretical approaches that match the existing data (Levin, 2020 ). Reports on remarkable recoveries range between cases that are (un-)related to HP but are medically verified (Engebretson et al, 2014 ), cases that are described on the Lourdes pilgrimage site (François et al, 2014 ) and self-reported narrative accounts of patients, to name just a few. The authors who endeavour to provide an explanation for HP, usually take an eclectic approach.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…These accounts indicate that biomedical, biopsychosocial and even holistic explanatory frameworks can be of use when addressing certain physiological, lifestyle and relational aspects of remarkable recoveries (see, e.g. Engebretson et al, 2014 about social connections), but they come short in describing the spiritual or the transformative experiences of the patients.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…These strong connections lead to an increased desire to live. 22 These cancer survivors also recounted a more pleasurable experience when connection remained intact throughout their illness. This retrospective, narrative study suggests having strong social connections might play a role in decreased mortality in cancer patients.…”
Section: Connection and Cancer Patientsmentioning
confidence: 99%
“…Connections help improve the life and health of cancer patients. In an article by Engebretson and colleagues, 22 cancer survivors of advanced stages of their diseases who lived an average 11 years after their initial diagnosis were all interviewed and major themes were pulled out of their narratives. The most obvious and consistent theme among all fourteen subjects was strong connections to family, friends, and medical staff.…”
Section: Connection and Cancer Patientsmentioning
confidence: 99%
“…Narratives are flexible and allow individuals to express their own views about their illness or the care they have received by occupying multiple positionalities and discourses (Mattingly, Lawlor, & Jacobs-Huey, 2002). At the same time, there are certain events in life, such as illnesses, and certain contexts, such as the hospital, which produce specific narrative types (Boaz & Morgan, 2014; Edvardsson, Rasmussen, & Riessman, 2003; Engebretson, Peterson, & Frenkel, 2013; Ewick & Silbey, 1995; Frank, 1995; Thomas, 2010; Tropea, 2012).…”
Section: Illness Narrativesmentioning
confidence: 99%